Crop development with data-driven approach towards sustainable agriculture: Lifting the achievements and opportunities of collaborative research between CIAT and Japan - Ogawa, Satoshi; Selvaraj, Michael Gomez; Ishitani, Manabu (Japan International Research Center for Agricultural Sciences, 2021)
International Center for Tropical Agriculture (CIAT) has a long history of collaboration with Japanese institutions to develop improved crop varieties and adopt agricultural technologies with pioneering approaches for farmers’ benefit. Since 1972, Japan has enjoyed a long history of successful cooperation with the CGIAR (formerly the Consultative Group on International Agricultural Research) after becoming its 22nd Member to meet global challenges such as climate change affecting agriculture and food systems in diplomacy through Japan’s advanced science and technology. This long-standing collaboration adopts agricultural technologies developed in Japan and promotes agricultural innovation through cutting-edge technologies such as remote sensing for Internet of Things (IoT) and Artificial Intelligence (AI) that will provide novel solutions to the agriculture and food sectors in the tropics. Nowadays, it is presumed that this approach to data-driven agriculture realization will help establish a sustainable agroecosystem with increased agricultural productivity and sustainability by adapting or mitigating the effects of climate change and efficient use of natural resources and establishing a sustainable food value chain. This review highlights the research collaborations and new opportunities on advanced breeding technologies and digital innovations towards data-driven agriculture. In conjunction, we present a potential collaborative research between CIAT and Japan, prioritizing the current and future challenges in agriculture and food systems.